The Digital Battlefield: A Comparative Analysis of AI-Driven Cyber Warfare in the U.S. and China and Its Implications for Pakistan’s National Security - Uswa Khalid (`, 2025)
The study explores the deepening U.S.-China competition in cyber warfare driven by artificial intelligence and its strategic consequences for Pakistan. Relatively smaller states such as Pakistan are forced to adapt and maneuver within a digitally contested security landscape, which is shifting due to the integrated use of AI innovations in military and cyber domains by both superpowers competing with one another through differing models of innovation, governance, and deployment. The research focuses on the U.S. and Chinese rival cyber strategies comprehensively around their doctrinal, operational, technological differences along with contextualizing them into the scenario of India-Pakistan conflict 2025 where AI-enabled warfare was crucial. Using offensive realism as the framework, the research highlights the impacts of structural forces that compel Pakistan to take advantage of Chinese technological backing while simultaneously being exposed to geopolitical-strategic dependency risks. Qualitative methods were used to identify policy gaps in response to dual vulnerabilities the urgent need for development that will lead to national resilience within ethical bounds and the lack of self-reliance in AI and cybersecurity drawn from literature reviews, policy analyses, and expert interviews. The conclusion outlines strategic autonomy as well as investments stressing proactive governance concerning digital design frameworks. It emphasizes cross-sector synthesized approaches responding to rising threats mounting at accruing strained interdependence framing peripheral states from dire subordinated status onto clear vision revealing new frontiers waiting exploration having transformative potential metamorphosing states like Pakistan sidelined into pivotal players drawing direct contribution shaping discourse on global asymmetrical dynamic rivalry headlined south-east continuum STEM as tributary fueling supers. Keywords: Artificial Intelligence (AI), Cyber Warfare, U.S.-China Rivalry, Pakistan National Security, Offensive Realism, Military-Civil Fusion, Strategic Autonomy, Digital Sovereignty, AI Ethics, Geopolitics